Transesophageal Echocardiography–Guided Epicardial Left Ventricular Lead Placement by Video-Assisted Thoracoscopic Surgery in Nonresponders to Biventricular Pacing and Previous Chest Surgery. Issue 3 (May 2018) - Schroeder, Carsten; Chung, Jane M.; Mackall, Judith A.; Cakulev, Ivan T.; Patel, Aaron; Patel, Sunny J.; Hoit, Brian D.; Sahadevan, Jayakumar
Abstract : Objective: The aim of the study was to study the feasibility, safety, and efficacy of transesophageal echocardiography–guided intraoperative left ventricular lead placement via a video-assisted thoracoscopic surgery approach in patients with failed conventional biventricular pacing. Methods: Twelve patients who could not have the left ventricular lead placed conventionally underwent epicardial left ventricular lead placement by video-assisted thoracoscopic surgery. Eight patients had previous chest surgery (66%). Operative positioning was a modified far lateral supine exposure with 30-degree bed tilt, allowing for groin and sternal access. To determine the optimal left ventricular location for lead placement, the left ventricular surface was divided arbitrarily into nine segments. These segments were transpericardially paced using a hand-held malleable pacing probe identifying the optimal site verified by transesophageal echocardiography. The pacing leads were screwed into position via a limited pericardiotomy. Results: The video-assisted thoracoscopic surgery approach was successful in all patients. Biventricular pacing was achieved in all patients and all reported symptomatic benefit with reduction in New York Heart Association class from III to I–II ( P = 0.016). Baseline ejection fraction was 23 ± 3%; within 1-year follow-up, the ejection fraction increased to 32 ± 10% ( P = 0.05). The mean follow-up was 566 days. The median length of hospital stay was 7 days with chest tube removal between postoperative days 2 and 5. Conclusions: In patients who are nonresponders to conventional biventricular pacing, intraoperative left ventricular lead placement using anatomical and functional characteristics via a video-assisted thoracoscopic surgery approach is effective in improving heart failure symptoms. This optimized left ventricular lead placement is feasible and safe. Previous chest surgery is no longer an exclusion criterion for a video-assisted thoracoscopic surgery approach.